A Dialysis of Human Personality and The Effect of Poverty on Character - Olubitan, Adesina Abiodun (KWASU Journal of Religious Studies, 2018)
The concomitant effect of poverty on the character of a person cannot be over-emphasised. Poverty and the array of socio-economic woes in the society portend grave capacity that damage and dehumanize the personality of an individual. A 'person' as a unit, loses personal ego and self. worth when the potential of what makes him/her a 'Person' and gives the individual voice and power in the society is lacking. In this scenario, a person's character which is tied to personality will suffer some indignity. In the context of economic power therefore, viz-a-viz; poverty, the character of a Person cannot be fully exhibited, hence, the person is prone to a character dentations and incapacitation. This paper, therefore, prods into the human personality in an attempt to conjecture the effect of poverty on the character of a person. If it can be said that the individual trait, character and temperament are the basic ingredients of personality; then it goes with the reason why personality reflects the different categories of people. Apparently, this explicates the purpose for having successful people and those who are not successful. The methods used in gathering data, are psycho-analytical, participatory observation, analytic and experiential.